Pengaruh Kecerdasan Emosional, Kecerdasan Spiritual dan Love of Money Terhadap Persepsi Mahasiswa Akuntansi Mengenai Etika Profesi Akuntan (Studi Empiris pada Mahasiswa Akuntansi Universitas Djuanda dan Universitas Pakuan) - Fauziah, Restu; Kusuma, Indra Cahya; Didi, Didi (Innovative: Journal Of Social Science Research, 2024)
This research is directed to examine the effect of emotional intelligence, spiritual intelligence and love of money on the perception of accounting students regarding the ethics of accounting profession; and analyze whether there are differences in these factors between accounting students at Djuanda University and Pakuan University. Data was collected through questionnaire distribution to 222 respondents selected based on purposive sampling. Data analysis was carried out with multiple linear regression and independent sample t-test using SPSS 25.0. The research findings reveal that emotional intelligence and spiritual intelligence have a significant positive effect on the perception of accounting students regarding the ethics of accounting profession, while love of money has no significant effect on the perception of accounting students regarding the ethics of accounting profession. The independent sample t-test shows no difference in emotional intelligence, spiritual intelligence, love of money and perceptions of the ethics of accounting profession between accounting students at Djuanda University and Pakuan University.